Pengaruh Perencanaan Pajak (Tax Planning), Intensitas Modal (Capital Intensity), dan Intensitas Persediaan (Inventory Intensity) terhadap Penghindaran Pajak (Tax Avoidance) (Studi Kasus pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indones - Putri Ayu; Ingra Sovita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
The population in this study consists of health sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, totaling 35 companies. The sampling technique used was probability sampling. The total number of observations used in the sample was 175 company year data, with 10 data points excluded, resulting in 165 observations. The analysis tool used in this study was SPSS 21. The results of this study show that the tax planning variable has a t-statistic value greater than the t-table 9,883 > 1,975 with a significance value of 0,000 < 0,05, indicating a positive and significant effect on tax avoidance. The capital intensity variable also shows a t-statistic value greater than the t-table -0,543 < 1,975 with a significance value of 0,594 > 0,05, indicating a positive and significant effect on tax avoidance. However, the inventory intensity variable has a t-statistic value lower than the t table 1,427 < 1,975 with a significance value of 0,156 > 0,05, indicating no effect on tax avoidance. Simultaneously, the variables of tax planning, capital intensity, and inventory intensity have an F-statistic value greater than the F-table 36,694 > 2,43 with a significance value of 0.000 < 0.05), indicating a positive and significant effect on tax avoidance.